Effects of binder concentrations and soaking time on combustion characteristics of briquettes produced from fermented gmelina arborea (roxb) sawdust and used print paper (2022)
Low-density briquettes are known for having several undesirable characteristics, such as an intense yellow flame and smokiness that are too high for domestic applications. The pretreatment of feedstock has been identified as a tool for addressing these issues; however, process costs and variability conditions has significant impact on the selection and performance of these methods. Consequent on these, fermentation method was employed to investigate the effects of binder concentration and soaking time on briquettes produced from fermented G. arborea sawdust and used print paper binder in this work. Untreated sawdust samples were collected from sawmill's dumpsite and soaked for 12, 24, 36, and 48 hours under mesophilic and anaerobic conditions while used print paper were converted into pulped fiber. Briquette mix ratio by percentage weight proportions varied from (10:90-50:50) % dry basis. A statistical analysis of briquette densities revealed a significant positive correlation between the densities of fermented briquettes and the binder concentration at (p<0.05). Thermal efficiency decreased with increase in binder concentration with no significant difference in fermentation time, while the specific fuel consumption increased with increase in binder concentration. Fermentation time and binder concentration slightly improved the combustion characteristics of briquettes. Economic analysis suggested economic viability of the process.